The Objectives of Harnessing and Developing the Earth in Islam (A Descriptive, Analytical, and Daʿwah-Oriented Study) - Dr Sabah Siddique; Dr Abdel Hamid Kharroub (Journal of Religion and Society, 2025)
In light of the rapid transformations and complex challenges affecting humanity’s relationship with the universe, with others, and with oneself, there arises a need to revisit the Islamic conception of human stewardship of the Earth through a deep and systematic reading—one that goes beyond functional or utilitarian aspects to the overarching purposes that guide human action and direct its civilizational impact. The concept of divine facilitation (al-taskheer) occupies a central position in this conception, as it carries theological, legal, and civilizational implications that establish a balanced understanding of humanity’s relationship with what has been made subservient to it in the cosmos. While Islamic studies have addressed the concept of taskheer in various contexts, much of this scholarship has focused on its cosmic manifestations or its economic and scientific effects, without delving into its broader objectives and legal functions within the framework of the higher purposes of Shariah. This highlights the central issue: uncovering the ultimate goals of divine facilitation, clarifying its role in shaping the believing human, guiding behavior, and fulfilling the human role in the stewardship of the Earth according to the divine paradigm. The article examines the concept of divine facilitation in light of the higher objectives of Shariah, viewing it as a value-based and duty-oriented framework that governs humanity’s relationship with the universe and establishes its role in the stewardship of the Earth according to the Islamic vision. It shows that taskheer is not limited to mere material empowerment but rests upon foundational beliefs that regulate human behavior, maintain balance between the unseen and the visible, and integrate reliance on God with taking practical measures. The article also emphasizes the devotional dimension of taskheer in translating theological principles into practical realities that contribute to reform and the building of a human society based on justice and peace. It concludes that caliphate (stewardship) represents the overarching purpose of the objectives of divine facilitation, which is realized only through the integration of both belief and devotional dimensions, within a framework characterized by comprehensiveness and balance, enabling humanity to cultivate the Earth and achieve happiness in both this life and the Hereafter. Keywords: Higher objectives of Shariah, divine facilitation, belief, propagation, caliphate, stewardship of the Earth.